Analisis Efisiensi Pemasaran Kerupuk Laweh di Nagari Sarilamak, Kecamatan Harau - Gusnita, Gusnita; Arnayulis, Arnayulis; Nefri, John (Agropross : National Conference Proceedings of Agriculture, 2023)
Kerupuk Laweh are a form of chips derived from processed cassava which are round (wide) in shape. Kandang Lamo Village, Sarilamak Urban Village, Harau District, Lima Puluh Kota Regency, is the center for the production of Kerupuk Laweh. This study aims to 1) identify marketing channels for Kerupuk Laweh in Sarilamak Urban Village, 2) identify margins and marketing efficiency for Kerupuk Laweh in Sarilamak Urban Village, 3) analyze farmer's share of Kerupuk Laweh in Sarilamak Urban Village. Sampling method was carried out in a saturated (saturated sample / census) and Snowball. The census method was used to determine the number of Kerupuk Laweh producers, that is as many as 30 people. The marketing channel for kerupuk laweh in Sarilamak Urban Village has 5 channel patterns: 1. Channels I and II have the same margin and farmer's share with a margin of IDR 36,500.00 with a percentage of 50.34%, the value of farmer's share is 49.66%. 2. Channel III has a marketing margin of IDR 26,500.00 with a percentage of 36.55%, the value of the farmer's share is 63.45%. 3. Channel IV has a margin of 24,500.00 percentage 33.79% 5 farmer's share 66.21%. 4. Channel V margin of IDR 0 with a percentage of 0,00% farmer's share is 100%.